DEVELOPMENT OF STUDENT WORKSHEETS WITH 4C SKILL-ORIENTED IN BIOLOGY SUBJECT (DEFINE PHASE IN SECOND GRADE OF SENIOR HIGH SCHOOL) - Inneke Putri Nowita; Rahmadhani Fitri; Yossi Lolita (Universitas Negeri Padang, 2021)
Industrial revolution 4.0 or also known as the Fourth Industrial Revolution (4IR). In facing the 4.0 revolution, someone must have skills, these skills are known as the 4Cs of 21st century learning, namely: communication, collaboration, critical thinking and problem solving, as well as creativity and innovation. These skills can penetrate the teaching and learning process, namely using teaching materials. Teaching materials that are often used are student worksheets. 4C skills can improve the activities that are on student worksheets. This study aims to determine and define the requirements needed in learning with content competence (KI), basic competence (KD), and learning materials according to the 2013 curriculum content standards. This type of research is a four-D model development research, but in This research only reaches the define stage. The subjects of this study were 60 students of class X SMA Negeri 1 Batusangkar. The results showed that developing student worksheets (LKPD) oriented 4C skills in class X semester 1 subjects.